Diacereína: desenvolvimento e validação de métodos de quantificação e dissolução - Borgmann, Sílvia Helena Miollo (2007)
Diacerhein (DAR) is a slow acting symptomatic drug used to treatment of osteoarthritis. It is available in the Brazilian market as capsules and compounded capsules. There are no official methods for DAR analysis in any of the pharmacopeia. In the present work, methods for the quantification and dissolution evaluation of the drug in capsules and compounded capsules were developed and validated. Spectrophotometry and high-performance liquid chromatography (HPLC) were the methods used for drug determination. In the spectrophotometric method the DAR can be quantified at 277 as well as 502 nm, using 0.1N NaOH as diluent. The HPLC analyses were performed on a C18 column, using a mobile phase composed of triethylamine 0.1%:acetonitrile (65:35, v/v; adjusted to 7.5 with orthophosphoric acid) and UV detection at 250 nm. The methods showed good linearity (r>0.99), precision (RSD<2%) and accuracy (>99%) and the results obtained were not statistically different (P=0.05). The optimization of dissolution test conditions for in vitro quality control of DAR in capsules was evaluated. The use of 900 mL of sodium phosphate buffer at 37.0 ± 0.5 ºC, basket as apparatus, at 100 rpm rotate speed and 30 minutes of test provided satisfactory results for tested products. The percent dissolution of DAR in the established condition was more than 80% and the different evaluated products presented good dissolution efficiency (>85%). The spectrophotometric method that was validated to evaluate the dissolution testing showed to be specific, with no interference of the placebo or shell capsules in the quantification of DAR, linear (0.27 6.66 μg mL-1; r>0.99), precise (RSD<5%) and accurate (>97%). The drug showed satisfactory stability in the selected dissolution medium.